International Fiscal Policy Coordination and GDP Comovement - Nicholas Sly; Caroline Weber (Center for Economic Studies and ifo Institute (CESifo), 2013)
Economic shocks often permeate borders generating comovement in nations' business cycles over time. We highlight the fact that fiscal policy coordination is an important avenue by which national economies become more integrated, influencing the transmission of macroeconomic shocks between countries. We find that changes in fiscal policy coordination - as measured by the signing of a bilateral tax treaty - increase business cycle comovement by 1/2 a standard deviation. This magnitude is one-and-a-half times larger than the effect of trade linkages, and is in sharp contrast to currency union membership, which has a near zero and statistically insignificant effect on business cycle comovement. We also find that new bilateral tax treaties increase comovement in shocks to nations' GDP trends, demonstrating the permanent effects of fiscal policy coordination.
Keywords: H87; F42; E62; 330